Stereologic estimation of Ki-67, caspase 3 and GSTP1 positive cells in prostate lesions - Santamaría, Luis (Image analysis and stereology, 2005)
Cell proliferation, caspase 3 and pi-form of glutathione S transferase (GSTP1)were evaluated in prostate carcinoma (PCA), proliferative inflammatory atrophy (PIA) and prostate intraepithelial neoplasia (PIN). Forty biopsies were classified as: without morphological lesions (controls: CTR), PIA, PIN and PCA. Ki67, caspase3 and GSTP1 were immunostained. The following estimates were performed: Numerical densities of Ki67+ cells (NvEPKi67), of all epithelial cells (NvEPtotal) and of GSTPI+ cells (NvEPGSTPI); labelling index for Ki67 (LIK;6`); volume fraction to caspase 3 positive tissue (Vvcaspase 3) and of GSTP1 positive tissue (V`GSTP1). ANOVA was performed to compare the groups. NvEPtotal and NvEPKi67 were increased in PIA. LIki67 was only increased in PCA. Vvcaspase 3 was decreased in PIN and PCA. VvEGSTP1 was decreased in PCA. In our results PIA lacks the characteristics of a premalignant lesion. The result may be explained by the use of unbiased quantitative methods, the inadequate definition of PIA and the scarce inflammation observed in the samples with PlA included in this study.
Keywords: Prostata, intraepitelijska neoplazija; Prostatic Neoplasms; Prostata, novotvorbe; Pathology; Ki-67 Antigen; Analiza variance; Celica, štetje; Glutathione Transferases; Prostatic Intraepithelial Neoplasia; Epitelij; Cell Count; Slika, obdelava z računalnikom; Epithelium; prostate; prostata; Cytology; rak (medicina); celice; Image Processing, Computer-Assisted; Analysis Of Variance; stereologija